Pengaruh Kompetensi Pustakawan Terhadap Kualitas Layanan Perpustakaan Pada Dinas Perpustakaan Dan Kearsipan Provinsi Bengkulu - Wansyah, Agistio; Saputra, Harius Eko; Maryaningsih, Maryaningsih (Professional: Jurnal Komunikasi dan Administrasi Publik, 2025)
This study aims to examine the extent to which librarian competence influences the quality of library services at the Library and Archives Office of Bengkulu Province. Librarian competence plays a vital role in ensuring high-quality information services to the public. This quantitative descriptive study employed data collection through questionnaires and documentation, involving 96 library users selected using incidental sampling. Data were analyzed using simple linear regression. The findings reveal a very strong correlation between librarian competence (independent variable) and service quality (dependent variable), with a correlation coefficient (R) of 0.854 and a determination coefficient (R²) of 0.729. This indicates that 72.9% of the variation in service quality is influenced by librarian competence, while the remaining 27.1% is influenced by other factors. The t-test confirms that this effect is statistically significant. These results highlight the importance of developing librarian competence, particularly in management, interpersonal communication, and information technology skills, as key strategies to improve public library service quality.